Factors influencing African students’ choice of studying in Malaysia: a case study in University of Science Malaysia (USM), Penang / Nur Farah Tajuddin - Tajuddin, Nur Farah (Faculty of Plantation and Agrotechnology, 2016)
In line with Malaysia’s aspiration to be a global education hub by the year 2020 along with the massive support from the Malaysian government, Malaysia has experienced an influx of foreign students in the local higher education institutions (Migin, Yajid, Khatibi, & Falahat, 2014). This study was conducted to determine the factors influencing African students’ choice of studying in Malaysia. The study is based on push and pull theory and the questionnaire was adapted by Mazzarol and Soutar (2002) which has been conducted on several related studies. A set of questionnaire consisting of 27 attributes (5 push attributes and 22 pull attributes) were administered and distributed to 200 respondents studying in University of Science Malaysia, Penang. Based on the attributes, the highest push factor was the desire to gain better understanding of Malaysia and the highest pull attribute were safe (low crime) environment. Relatively, most students were influenced more by the pull factors compared to the push factors.